Peranan Big Five Personality dan Fear of Failure Terhadap Sport Performance pada Pemain Futsal Universitas Di Jakarta - Tanawi, Suhiandy Sulaiman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
ABSTRACTThe aim of this study is to know the role of big five personality and fear of failure in sport performance of futsal players who are still as students in Jakarta. This study uses quantitative method and data are collected by questionnaires which involved students who are members of futsal extracurricular and have participated in regional tournaments (N=103). Three questionnaires are used in this study. Personality was assessed by using Big Five Inventory (BFI), fear of failure was assessed by using Performance Failure Appraisal Inventory (PFAI), and sport performance was assessed by coach’s rating. The results showed that conscientiousness have significant role on sport performance ((?= .333, p < 0.05), while the fear of failure variable have no role in sport performance.